"Activated Borane" – A Porous Borane Cluster Network as an Effective Adsorbent for Removing Organic Pollutants. Issue 67 (7th October 2022) - Bůžek, Daniel; Škoch, Karel; Ondrušová, Soňa; Kloda, Matouš; Bavol, Dmytro; Mahun, Andrii; Kobera, Libor; Lang, Kamil; Londesborough, Michael G. S.; Demel, Jan
Abstract: The unprecedented co‐thermolysis of decaborane(14) ( nido ‐B10 H14 ) and toluene results in a novel porous material (that we have named "activated borane") containing micropores between 1.0 and 1.5 nm in diameter and a specific surface area of 774 m 2 g −1 (Ar, 87 K) that is thermally stable up to 1000 °C. Solid state 1 H, 11 B and 13 C MAS NMR, UV‐vis and IR spectroscopies suggest an amorphous structure of borane clusters interconnected by toluene moieties in a ratio of about three toluene molecules for every borane cluster. In addition, the structure contains Lewis‐acidic tri‐coordinated boron sites giving it some unique properties. Activated borane displays high sorption capacity for pollutants such as sulfamethoxazole, tramadol, diclofenac and bisphenol A that exceed the capacity of commercially‐available activated carbon. The consistency in properties for each batch made, and the ease of its synthesis, make activated borane a promising porous material worthy of broad attention. Abstract : Porous polymer : Thermolysis of nido ‐B10 H14 and toluene at 250 °C affords the novel microporous polymer named "activated borane". Analyses suggests an amorphous structure of borane clusters interconnected by toluene moieties. Activated borane displays a high surface area of 774 m 2 g −1, thermal stability under Ar up to 1000 °C, and sorption capacity to emerging pollutants exceeding the capacity of commercial activated carbon.